721. Effect of Gastrointestinal Pathogen Panel (GIP) in Antibiotic Management. (31st December 2020) - Saling, Christopher F; Seville, Maria T; Patron, Roberto L
Abstract: Background: GIP offers detection via PCR for a wide array of common microbes associated with diarrheal illness. Its rapid turnaround time and high sensitivity has made GIP testing commonplace for the evaluation of diarrhea. The purpose of this study is to determine if GIP influences antibiotic management in patients hospitalized with diarrhea. Methods: Fifty patients hospitalized at Mayo Clinic Arizona between July and December 2019 who underwent BioFire® FilmArray™ GI PCR Panel testing were randomly selected. Medical records were reviewed to capture gender, age, immunocompromised state, antibiotic use within 30 days, prior hospitalization within 3 months, history of Clostridioides difficile infection, time from admission to testing and GIP results, and to determine if GIP results directly contributed towards antibiotic management. This study was exempt from Institutional Review Board approval. Results: Twenty-six patients were male and twenty-four were female. The average age was 61.7 years. Thirty-four patients (68%) were immunocompromised. Forty-one GIPs were ordered within 24 hours of admission. Twenty-two patients (44%) had a positive GIP result; five were positive for 2 concurrent organisms. C. difficile was the most commonly detected organism, found in 16/24 (66.7%) positive tests. Eleven patients (68.8%) with C. difficile had a recent hospitalization, antibiotics within 30 days, or a history of C. difficile infection. There were 3 cases of Enteropathogenic Escherichia coli, 2 of Enterotoxigenic Escherichia coli, 2 of adenovirus, 2 of norovirus, 1 of rotavirus, and 1 of Vibrio cholerae . Excluding C. difficile positive patients, GIP testing contributed in changing antibiotic management in 3/50 (6%) patients tested. One patient had antibiotics stopped, one received correct antibiotics, and one received inappropriate antimicrobial therapy. Conclusion: These results suggest that except in the setting of C. difficile infection, GIP has little utility in guiding antimicrobial management, even in the immunocompromised patient. GIP testing is expensive and it may be more resourceful to screen patients hospitalized with diarrhea for C. difficile alone, especially in those with risk factors for C. difficile infection. Furthermore, GIP testing can lead to antibiotic overuse. Disclosures: All Authors : No reported disclosures